(untitled) (Prosiding Keislaman dan Sains, 2025)
This study aims to examine the correlation between leadership style, organizational culture, and job satisfaction with teacher organizational commitment in Madrasah Aliyah Negeri Riau Islands Province, both partially and simultaneously. This research is a quantitative study with a survey method conducted at MAN in Riau Islands, a population of 155 people and a sample using total sampling. The hypothesis in this study is that leadership style, organizational culture, and job satisfaction have a significant correlation both partially and simultaneously to teacher organizational commitment. Hypothesis testing uses Pearson Product Moment Correlation technique analysis and multiple regression, with a significant level of alpha 5 percent (α = 0.05). This study produces findings, namely: leadership style variables have a correlation with teacher organizational commitment. It can be concluded that: leadership style has a correlation with teacher organizational commitment. The implication is that the better the leadership style, the higher the organizational commitment of teachers. Based on the SPSS data output above, the pearson correlation value is 0.537. Then r count 0.537> r table 0.178 so it can be said that the two variables are related or by looking at the sig value. 0.000 <0.05, then correlated. So it can be said that X1 and Y have a relationship. With the degree of relationship the value of 0.537 is in a moderate correlation and the form of the relationship is positive. This means that the higher the leadership style, the greater the organizational commitment and vice versa.